(untitled) (Texas Journal of Engineering and Technology, 2026)
In this article Data on the study of the effect of artificial air ionization on the process of reviving mulberry silkworm eggs in the spring of 2025. The results of scientific and practical research on determining the optimal air ion concentration are also presented.